2016
DOI: 10.18632/oncotarget.7908
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a and miR-144 inhibit proliferation and metastasis of esophageal squamous cell cancer by inhibiting cyclooxygenase-2

Abstract: The altered expression of miRNAs is involved in carcinogenesis of esophageal squamous cell carcinoma (ESCC), but whether miRNAs regulate COX-2 expression in ESCC is not clear. To this end, the expression levels of miR-26a and miR-144 in ESCC clinical tissues and cell lines were investigated by qRT-PCR. COX-2 and PEG2 were quantified by western blot and ELISA. Decrease in miR-26a and miR-144 expression in ESCC was found by a comparison between 30 pairs of ESCC tumor and adjacent normal tissues as well as in 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 88 publications
4
30
0
Order By: Relevance
“…Increased cytochrome c oxidase subunit II (COX-2) expression has been linked to the initiation and progression of human (11), and COX-2 has been reported to play a key role in the apoptosis of cancer cells (12). In the present study, it was found that miR-26a was significantly downregulated in prostate cancer tissues.…”
Section: Introductionmentioning
confidence: 48%
“…Increased cytochrome c oxidase subunit II (COX-2) expression has been linked to the initiation and progression of human (11), and COX-2 has been reported to play a key role in the apoptosis of cancer cells (12). In the present study, it was found that miR-26a was significantly downregulated in prostate cancer tissues.…”
Section: Introductionmentioning
confidence: 48%
“…Hence, identification of miRNAs and their target genes involved in tumorigenesis will provide key clues for the development of novel diagnostic tools and therapies for patients with cervical cancer. miR-144 is located on chromosome 17q11.2 of the human genome, which has been reported to be downregulated in esophageal squamous cell cancer (28), laryngeal squamous cell carcinoma (29), lung cancer (30) and bladder cancer (31). The present study assessed the expression levels of miR-144 in cervical cancer tissues and their matched normal cervical tissues to determine the effects of miR-144 on the malignant progression of cervical cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have confirmed that miRNAs can regulate the stability and translation of their target mRNAs by attaching to the 3'UTR of the target [6]. In addition, it has been proven that these miRNAs, including miR-21, miR-138, miR-223 and miR-92a, regulate ESCC development through the regulation of the expression of their target genes, such as PTEN (phosphatase and tensin homolog), FBXW7 (F-box and WD repeat domain containing 7) and PDCD4 (programmed cell death 4) [8]. In this study, we used a luciferase reporter assay to demonstrate that miR-543 was capable of directly targeting the 3'-UTR of PLA2G4A, and the results showed that PLA2G4A is a target of miR-543.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Several studies have identified by there are many kinds of miRNAs with variable expression in human tumor tissues [7]. As we know from other studies, some miRNAs act as tumor facilitators, whereas others act as inhibitors [8]. Although these two types of miRNAs lead to different results, they both play decisive roles in various aspects of the progression of carcinogenesis, including invasion and migration [3,9].…”
Section: Introductionmentioning
confidence: 99%